Contract Farming of Potato in Punjab: A Comparative Study - Geetanjali,; Kumar, Pankaj; Kaur, Prabhjot (Indian Journal of Extension Education, 2025)
The  study was conducted in Hoshiarpur district in Punjab during year 2019-2020. Data were collected from 98 respondents who were practicing contract farming and noncontact farming of potato. The study revealed that all the contract farmer respondents had purchased their seeds from the contracting agency while the majority of non-contract respondents purchased their seeds privately which was significantly different. All the contract respondents had used FC 3 (FL1867) variety whereas 77.55 per cent of noncontact respondents used the Kufri Pukhraj variety (an early sown variety). All the contract respondents followed more than recommended row to row-R spacing whereas the majority of non-contract respondents followed the recommended spacing which shows that data was varying significantly. In contract respondents, the majority had harvested their crop in 70-80 days whereas 71.49 per cent of non-contract respondents harvested their crop in 60-70 days. Majority of contract and non-contract respondents got a yield of about 90-120 q/acre.